The Behavior of Foreign Exchange Rates – Comment - So, Jacky C. (Journal of International Business Studies, 1986)
The distributors of foreign exchange rates are important for model building and empirical analysis. For example, many studies have examined foreign exchange market efficiency and currency portfolio management under the assumption that foreign exchange rates are normally distributed. The statistical tests in these studies, and thus their conclusions, may not be reliable if the foreign exchange rates follow non-normal distributions. Realizing the importance of the distribution of exchange rates, Professors Calderón-Rossell and Ben-Horim (1982) (hereafter C-B) have conducted a study analyzing these distributions. Based on the skewness of the distribution, C-B have classified foreign currencies into three groups. In the first group, the skewness statistic was not significantly different from zero for all currencies and subperiods. In the second group, the distribution of changes in the foreign exchange rates was close to symmetric except for at least one subperiod. In the third group, the skewness statistic suggests strongly that all the distributions were asymmetric. Their results reveal that: